Importance of Dynamic Capabilities: Literature Review - Mike AZEVEDO; Jorge SIMÕES; Ruben LOUREIRO (Communications of International Proceedings, 2021)
Currently, companies must be prepared for any unexpected change that threatens their position and economic situation. For this to be possible, companies must hold and develop Dynamic Capabilities to manage their resources in the best way and so that it can develop and implement strategies, to be able to compete in constantly changing markets with the purpose of achieving good economic performance. The following article seeks to reinforce the existing literature in Strategic Management with research focused on Dynamic Capabilities.
Keywords: Dynamic Capabilities; Resources; Strategic Management.